TRANSFORMATION OF SOCIAL INSTITUTIONS IN CRISIS CONDITIONS - Kurnosenko, Larysa (Public Administration and Regional Development, 2022)
The article synthesizes the opinions of scientists regarding the understanding of crisis as a phenomenon, considers approaches to the transformation of social institutions in crisis conditions and the influence of individual and collective actions integrated into the activities of social institutions on their transformation. Attention is focused on the fact that the transformation process takes place as a result of the expansion and strengthening of ties between social institutions, collective and individual actions, as internal and external conductors of changes in crisis situations. On the basis of the structural integration model, it is illustrated how, in the conditions of crises, these connections help the leaders of change to direct their actions not only to achieve stability, but also to the further development and transformation of social institutions. It is emphasized that the transformation of social institutions means a profound change not only in the external, in relation to a person, environment, it also involves a change in his values, perceptions, attitudes, which occurs, as a significant number of sociological studies show, not only under the influence of exogenous factors, but is the result of internal changes, which in turn are a reaction to the crisis. Some aspects of interactions between internal and external drivers of change are considered, leading to the transformation of social institutions, which occurs as a result of the search for ways to overcome the crisis at the individual and systemic levels. Accordingly, created models of crisis resolution should take in to account the nature of interactions between internal and external drivers of change.